(untitled) (ASEAN Engineering Journal, 2016)
Wide range input voltage converters are merely required in photovoltaic and wind energy conversion systems which have dynamic output voltage due to irradiance and wind speed fluctuations. This paper presents a comprehensive analysis and design approach of grid connected buck-boost inverter for wide input voltage application. Sizing of a LC output filter component is emphasized in this paper. It is important to size the filter properly to obtain a trade-off between output current ripple and reactive power supplied into grid when inverter is in stand-by mode. A graphical method is employed to determine filter parameters. The presented method is found to be straight forward and easy from practical point of view.